Hemoperitoneum caused by bleeding of adenomyosis: a case report - Su-Xian Zhang; Lu Wu; You-Fang Hou; Bo Yan; Shao-Yan Yang; Li-Hua Yang; Qing-Hua Zhao (Clinical and Experimental Obstetrics & Gynecology)
Rationale: Adenomyosis is a disease in which the endometrial tissues (glands and stroma) extend into the myometrium. It usually occurs in parous women aged 35 to 50 years old. The common symptoms include secondary severe dysmenorrhea and menorrhagia. Hemoperitoneum is extremely rare and easily overlooked. Patient concerns: A 46-year-old woman had adenomyosis and hemoperitoneum caused by bleeding of adenomyosis. Diagnoses: Adenomyosis and hemoperitoneum. Interventions: Hysterectomy with unilateral adnexectomy and subcutaneous injection of GnRH-α every 28 days for 3 times. Outcomes: The patient recovered well after the operation and was asymptomatic for 3 months after the operation. Lessons: We reported a case of adenomyosis in a parous woman. This patient received surgery because hemoperitoneum caused by bleeding of adnomyosis. It was important to timely diagnose and treat.